2011
DOI: 10.1177/1069397110393313
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Analysis of Models of Romantic Love Among U.S. Residents, Russians, and Lithuanians

Abstract: Our goal was to detect and describe a common "core" structure of romantic love and to also discover and explain variations due to cultural or gender differences between three national cultures: the United States, Russia, and Lithuania. Our sample consisted of 262 American males, 362 American females, 166 Russian males, 130 females, 102 Lithuanian males, and 135 Lithuanian females-a total of 1,157 people. Our analysis was derived from (a) a 14-item questionnaire; (b) freelist responses to the question "What do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
67
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 19 publications
11
67
1
1
Order By: Relevance
“…(De Munck et al, 2010) The Chinese youth survey, with the exception of the gender difference found in the response to the question "I will do anything for my lover," lends further support to de Munck's Euro-American core attributes of love findings (see Table 3). We did find, however, a cultural shift in the value placed on romantic love (see note 1).…”
Section: Resultssupporting
confidence: 54%
“…(De Munck et al, 2010) The Chinese youth survey, with the exception of the gender difference found in the response to the question "I will do anything for my lover," lends further support to de Munck's Euro-American core attributes of love findings (see Table 3). We did find, however, a cultural shift in the value placed on romantic love (see note 1).…”
Section: Resultssupporting
confidence: 54%
“…The study found that 90% of Lithuanians reported that they fell in love within a month or less, whereas 58% of Americans fell in love within a time frame of two months to a year (de Munck, Korotayev, de Munck, & Khaltourina, 2011). Other data is worthwhile to note in this context.…”
Section: Experience Of Love and Being In Lovementioning
confidence: 82%
“…De Munck, Korotayev, de Munck, and Khaltourina (2011) compared the United States, Lithuania, and Russia. They found that people from all three countries agreed on the following characteristics as the "core" of romantic love: (1) the eros component of love (physical attraction), (2) the essence of altruistic love (agape), (3) the tendency of lovers to engage in intrusive thinking about the beloved, (4) a concept of transcendence: the feeling that the union of two lovers results in something more meaningful than just the two lovers.…”
Section: Experience Of Love and Being In Lovementioning
confidence: 99%
“…From a cultural perspective, Lindholm identifies three main cultural configurations of love, the first in hierarchical and internally competitive societies, in which marriage is a political matter and romantic relations are always adulterous and commonly non-sexual; the second in individualistic, fragmented, fluid societies in which love and marriage go together; and the third in highly structured, disharmonic societies in which romantic ties between youth are severed by arranged marriages 23. ‘Love’ is, then, culturally shaped by the society in which it occurs and is socially sculpted to fulfil specific needs 24. There is, for example, evidence that people who embrace an ‘institutional model’ of marriage, as opposed to a purely ‘soulmate’ model, experience specific benefits to their relationship25 and that understandings of the key concepts of ‘soulmates’, compatibility and intimacy are also socially conditioned and, as a result, subject to change over the course of history 26…”
Section: Narcissism and Shamementioning
confidence: 99%